Development of standardization methods of gel with sapropel extract and their validation - Strus, Oksana; Revyatskyy, Ivan; Holota, Serhii; Gushcha, Sergey (Current Issues in Pharmacy and Medical Sciences, 2023)
Humic acids (HA) are important natural compounds that are characterized by a wide range of biological activity and therapeutic impact on different pathological processes. Sapropels are natural healing resources that contain a large amount of HA. The pharma-ceutical market of Ukraine needs domestic drugs with dermatotropic action based on natural compounds that have a combined antibacterial, wound healing and anti-inflammatory activity, as well low toxicity.The aims of the research: standardization of the gel under the conditional name "Saprogel" for use in medicine as a wound-healing and anti-inflammatory agent, development of methods for identification and quantification, as well as their validation.A linear dependence between the concentration of the total mass fraction of HA on the mass of the sample of aqueous sapropel extract (ASE) with a correlation coefficient of 0.9985 (≥0.9981) was observed, while the angular coefficient of linear dependence (b) was found to be 1.02, with the free member of linear dependence (a) being – 1.66≤2.60. The obtained results show that the method is precise because the value of the relative confidence interval is less than the critical value for the convergence of the results: Δ%=1.27≤1.60 and the criterion of the insignificance of systematic error: δ=0.51. As a result of the quantitative analysis, we found that the total mass fraction of HA in the gel samples from the wind farm is 1.302%.